Macrophages in obesity - Pirzgalska, R; Domingos, A (Elsevier, 2018)
Obesity is a worldwide public health concern yet no safe therapies are currently available. The activity of sympathetic neurons is necessary and sufficient for fat mass reduction, via norepinephrine (NE) signaling. Macrophage accumulation in the adipose tissue is thought to play the central role in the onset of obesity, yet their relation to NE has been controversial. We have identified a population of sympathetic neuron-associated macrophages (SAMs) that control obesity via the uptake and clearing of NE. Here we focus on the neuro-immune regulation of obesity by discussing the genetic, cellular and functional signatures of SAMs vis-a-vis adipose tissue macrophages (ATMs).